2019
DOI: 10.1098/rstb.2019.0080
|View full text |Cite
|
Sign up to set email alerts
|

Emergent microscale gradients give rise to metabolic cross-feeding and antibiotic tolerance in clonal bacterial populations

Abstract: Supplemental Figure 1. Nutrient gradients and gene expression are reproducible across replicates. The figure shows the profiles of single cell growth rate (left), normalized ptsG expression (middle), and normalized acs expression (right) for wildtype (WT, top) and acs mutant populations (bottom), each line shows average values within a single replicate (six to ten chambers). Note that overall profiles are very similar between replicates, though some are shifted slightly towards higher or lower depth (e.g. dar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
75
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(83 citation statements)
references
References 38 publications
3
75
0
Order By: Relevance
“…In previous work, we showed that when glucose is supplied at low concentration in the flow channel (800 mM), the combined metabolic activity of the cells creates strong nutrient gradients along the depth of the chamber [34]. The local microenvironment varies over a length scale of a few cell lengths, and, as a result, the average phenotype of the cells changes with the depth in the chamber.…”
Section: Subpopulations Specialize In Different Metabolic Activities mentioning
confidence: 99%
See 2 more Smart Citations
“…In previous work, we showed that when glucose is supplied at low concentration in the flow channel (800 mM), the combined metabolic activity of the cells creates strong nutrient gradients along the depth of the chamber [34]. The local microenvironment varies over a length scale of a few cell lengths, and, as a result, the average phenotype of the cells changes with the depth in the chamber.…”
Section: Subpopulations Specialize In Different Metabolic Activities mentioning
confidence: 99%
“…All experiments were done with E. coli MG1655 carrying the low copy number pSV66-acs-gfp-ptsG-rfp plasmid, which contains a GFPmut2 transcriptional reporter for acs and a turboRFP transcriptional reporter for ptsG [34].…”
Section: Strains and Plasmidsmentioning
confidence: 99%
See 1 more Smart Citation
“…The complexity of these communities might partly reflect the complexity of their environment, which can generate and maintain diversity by allowing specialisation on different niches [1][2][3][4][5][6][7][8][9][10] . Experimental evolution has shown how initially clonal populations can adaptively diversify into stably coexisting ecotypes, each specialised on pre-existing niches defined by available nutrients 1 , spatial structure 2,11 , temporal variability such as the feast and famine cycles in serial transfer [3][4][5][6][7][8][9] , or combinations thereof 10 . However, even in constant, unstructured environments with a single limiting carbon source metabolic diversification routinely evolves 4,[12][13][14] .…”
mentioning
confidence: 99%
“…Here, microfluidics or micromodels are promising tools to mimic soil pore structure especially when combined with new imaging techniques allowing for small-scale observations (Aleklett et al, 2018;Baveye et al, 2018). Recently, Co et al (2019) applied microfluidics and observed an increase in antibiotic tolerance in spatially structured compared to intermixed populations (Co et al, 2019). However, the usage of microfluidics is an emerging field and until fully established, the application of simulation models to investigate microscale spatial disturbance effects is a powerful tool.…”
Section: Modeling Spatially Structured Disturbancesmentioning
confidence: 99%